Investigation of MIG welding to the corrosion behaviour of carbon steel - Ng, Wai Loon (2012)
A welding process was performed on the low carbon steel based on different welding parameters in this experiment. The main objective of this study was to investigate the effect of welding voltages (19 V, 20 V, 21 V, and 22 V) and wire feed rates (90 ipm, 100 ipm, 110 ipm, and 120 ipm) to the corrosion behaviour of welded carbon steel in synthetic seawater environment (3.5 wt% NaCl). Besides that, the microstructure changes in the weldments of maximum and minimum voltages were analysed and compared with the as-received sample before welding process. On the other hand, the penetration level of the weldments was analysed due to the different welding parameter. The welding method in this experiment was metal inert gas (MIG) with filler metal (ER 70S-6 with 1.2 mm diameter). Based on the results obtained, the corrosion rate decreased when the welding voltage was increased from 19 V to 22 V or when the wire feed rate was increased from 90 ipm to 120 ipm until the full penetration level of weldment occurred. In conclusion, the lowest corrosion rate occurred at highest welding voltage and highest wire feed rate when full penetration of weldment occurred. The corrosion product that formed on the surface of the sample was iron oxides and pitting was found on the surface of the exposed area after the corrosion test.